Via Cairo, Tel Aviv, Athens, and Other Places, too: Early Modernist Architecture in Colonial Cyprus - Danos, Antonis (My University, 2022)
The paper looks at architecture in (British) colonial Cyprus, between 1930 and 1960 (when the island became an independent republic), when art deco and other early modernist buildings (both private houses and public-use structures) were constructed on the island. The analysis foregrounds a process that interrogates the classical (hegemonic) narrative of one-way traffic between the (central and western) European “centres” to the (in this case, eastern Mediterranean) “peripheries”; instead, it presents modern architectural manifestations as the result of a network of multi-directional “influences”, “translations”, (local) modifications, crossings and trans-culturations. These involved not only architects and architectural aesthetics, but also, migrants, merchants, entrepreneurs, and urban professionals, along with economic, social and ideological concerns, in a network where Cypriot towns interacted, directly and simultaneously, with several eastern Mediterranean centres (Cairo, Alexandria, Tel Aviv, Athens etc.), just as young Cypriot architects were bringing, to the island, expertise acquired in various western cities.
Keywords: Architecture; Modernist; Cyprus; Eastern Mediterranean